A Novel Technique to Retrieve Cement Retained Implant Supported Prosthesis with Digital Imaging: A Technical Report - Kapil Raju; Fathima Raza; Anand Kumar Vaidyanathan (Journal of Dentistry)
Retrievability of cement-retained implant-supported prosthesis in the event of abutment screw loosening is a challenging task, and the most common arbitrary drilling technique to retrieve the prosthesis can cause extensive irreversible damage. A 37-year-old male patient reported a chief complaint of a mobile implant-supported prosthesis in the left upper back tooth region. Past dental history revealed that the patient had underwent replacement of missing 27 using cement-retained implant-supported prosthesis 4 years ago using digital impression technique and Computer Aided Designing-Computer Aided Manufacturing (CAD-CAM) milling. This case report describes a novel technique to locate the screw access channel and fabrication of three-dimensional (3D) printed guide template that retrieved the cement-retained prosthesis utilizing the stored digital imaging data. The technique involves designing of the virtual model, screw access channel locator, and prosthesis using CAD technology with the digital impression made during prosthesis fabrication.